Analysis of Work Environment, Work Discipline, And Work Spirit on The Performance Of Teachers at Sma Negeri 2 Binjai - Muharani Aprilia; Sri Rahayu; Soulthan Saladin Batubara (International Journal of Management, Economic and Accounting, 2025)
This research was conducted with the aim of determining the influence of the work environment, work discipline and work spirit on the performance of SMA Negeri 2 Binjai teachers. The population in this study is the teacher of SMA Negeri 2 Binjai. The number of samples used was 82 people. This study uses a quantitative associative research approach. Data collection was carried out by distributing questionnaires. The research data used SPSS 25.0. The results of the research show that work environment, work discipline and work spirit have a positive and significant effect on the performance of SMA Negeri 2 Binjai teachers both partially and simultaneously. The Work Environment partially has a positive and significant effect on the Performance of SMA Negeri 2 Binjai Teachers, with a work environment value of 2.493 > 1.991 and a significant 0.015 < 0.050, so that H1 is accepted. Work discipline partially had a positive and significant effect on the performance of teachers of SMA Negeri 2 Binjai with a work discipline score of 3.727 > 1.991 and a significance of 0.000 < 0.050, so H2 was accepted. Work spirit partially had a positive and significant effect on the performance of teachers of SMA Negeri 2 Binjai with a Work Discipline score of 2.752 > 1.991 and a significance of 0.007 < 0.050, so H3 was accepted. work environment, work discipline and work spirit have a positive and significant effect on the performance of SMA Negeri 2 Binjai teachers simultaneously. Where the > value , 43,070 > 2,722 at a significance of 0.000 < 0.05. Therefore, H4 was accepted. The conclusion that can be drawn is that the hypotheses H1, H2, H3 and H4 are proven to be true and acceptable because the results of the research are in line with the hypothesis proposed.t_{hitung}t_{hitung}t_{hitung}F_{hitung}F_{tabel}